DESIGN AND CONSTRUCTION OF CAR RENTAL MONITORING SYSTEM BASED ON MICROCONTROLLER INTEGRATED THROUGH SMARTPHONE USING FUZZY MAMDANI METHOD - Rakhmat Kurniawan R; Abdul Halim Hasugian; Alwy Azyari Harahap (Sean Institute, 2022)
The increasing human needs to follow human needs as well as the lack of employment opportunities make some people do the theft mode. Some of them are by borrowing a car rental, but in certain cases the borrower does not return the car or it can be called as running away or stealing with borrowed mode. Therefore, the author wants to make a tool that can monitor the car remotely using a microcontroller, where the MPU-6050 sensor will be used to determine the status of the car when it is on, off, and running. The Ublox Neo6M GPS module will also be used to track the car's location. The output to be received will be sent through the intermediary of the 800L SIM module. In this study using the Mamdani fuzzy method because this method is suitable for use in most real-time problems such as making decisions to look for engine vibrations in cars that change and are less certain. In this study, the average percentage difference between the MPU-6050 sensors is 6.722%. With this fuzzy logic method, a mathematical framework is obtained that is used to represent uncertainty, ambiguity, imprecision, lack of information and partial truth. Keywords: Monitoring System, Car Rental, Microcontroller, Fuzzy Mamdani.